Seminar on information is our business and palmoilis hands-on user training, 16 Nov 1995, Palm Oil Research, Institut of Malaysia, Bangi - Institut Penyelidikan Minyak Kelapa Sawit Malaysia; Malaysia. Kementerian Perusahaan Utama (Bangi : PORIM, 1995)
22